Capulavirus and Grablovirus: two new genera in the family Geminiviridae - Varsani, Arvind; Roumagnac, Philippe; Fuchs, Marc; Navas-Castillo, Jesús; Moriones, Enrique; Idris, Ali; Briddon, Rob W.; Rivera-Bustamante, Rafael; Murilo Zerbini, F.; Martin, Darren P (Archives of virology, 2017)
Geminiviruses are plant-infecting single-stranded DNA viruses that occur in most parts of the world. Currently, there are seven genera within the family Geminiviridae ( Becurtovirus , Begomovirus , Curtovirus , Eragrovirus , Mastrevirus , Topocuvirus and Turncurtovirus ). The rate of discovery of new geminiviruses has increased significantly over the last decade as a result of new molecular tools and approaches (rolling-circle amplification and deep sequencing) that allow for high-throughput workflows. Here, we report the establishment of two new genera: Capulavirus , with four new species ( Alfalfa leaf curl virus , Euphorbia caput-medusae latent virus , French bean severe leaf curl virus and Plantago lanceolata latent virus ), and Grablovirus , with one new species ( Grapevine red blotch virus ). The aphid species Aphis craccivora has been shown to be a vector for Alfalfa leaf curl virus , and the treehopper species Spissistilus festinus is the likely vector of Grapevine red blotch virus . In addition, two highly divergent groups of viruses found infecting citrus and mulberry plants have been assigned to the new species Citrus chlorotic dwarf associated virus and Mulberry mosaic dwarf associated virus, respectively. These species have been left unassigned to a genus by the ICTV because their particle morphology and insect vectors are unknown.